Differential Equations and Linear Algebra (4th Edition)

Published by Pearson
ISBN 10: 0-32196-467-5
ISBN 13: 978-0-32196-467-0

Chapter 2 - Matrices and Systems of Linear Equations - 2.3 Terminology for Systems of Linear Equations - Problems - Page 144: 3


See below.

Work Step by Step

Plugging in the values into the equations: $(1-t)+(2+3t)+(3-2t)=(1+2+3)+(-t+3t-2t)=6$ $(1-t)-(2+3t)-2(3-2t)=(1-2-6)+(-t+-3t+4t)=-7$ $5(1-t)+(2+3t)-(3-2t)=(5+2-3)+(-5t+3t+2t)=4$ All of the equations are satisfied, thus it is in fact a good solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.